Present and prospects for multi-aged silviculture in Chilean temperate forests: Targeting secondary forests in transition and partially harvested old-growth forests - Donoso, Pablo J.; Soto, Daniel P.; Salas-Eljatib, Christian; Riquelme-Buitano, Tomás R. (Frontiers in Forests and Global Change, 2022)
Valdivian Temperate Rainforests in Chile have a global conservation value, but nowadays many correspond to secondary forests following regeneration in agricultural and burned lands, and to high-graded old-growth due to mismanagement, especially at mid to low elevations. Perspectives for increasing old-growth attributes in these productive forests through silviculture are high considering the diverse demands of ecosystem services and the high timber value of tree species. In the Llancahue experimental forest (40o S Lat) we implemented three ecological silviculture approaches: variable-density thinning in a Nothofagus dombeyi secondary forest (NDS), irregular shelterwood in a mature N. dombeyi forest (NDM), and single-tree selection cutting in a partially harvested old-growth forest (OG). Based upon an old-growth index (OGI) that includes density, basal area (ba), ba of the trees > 80 cm in diameter, ba of shade-tolerant species, and the Gini coefficient, and aims to estimate how close a given forest is to a typical old-growth forest, these forests had a 22, 22 and 62% OGI before management. The OGI remained similar or declined following management, but 7-10 yr after management it increased in NDS and NDM and declined in the OG (significant changes only in NDM and OG). We discuss these results considering that managed forests should target for an OGI ≈70% rather than maximum values. These managed forests contribute to halt degradation, mitigate climate change (carbon stores in the forest and in timber), and may have greater adaptive capacity to disturbances. We discuss perspectives for the potential scale-up of implementing these approaches.